Developing an Open Social Scholarship Collaboration: Lessons from INKE - Siemens, Lynne (KULA)

(untitled) (University of Victoria Libraries, 2019)
Many academic teams and granting agencies undergo a process of reflection at the completion of research projects to understand lessons learned and develop best practice guidelines. Generally completed at the project’s end, these reviews focus on the actual research work accomplished with little discussion of the work relationships and process involved. As a result, some hard-earned lessons are forgotten or minimized through the passage of time. Additional learning about the nature of collaboration may be gained if this type of reflection occurs during the project’s life. Building on earlier examinations of INKE, this paper contributes to that discussion with an exploration of seventh and final year of a large-scale research project.Implementing New Knowledge Environment (INKE) serves as a case study for this research. Members of the administrative team, researchers, postdoctoral fellows, graduate research assistants, and others are asked about their experiences collaborating within INKE on an annual basis in order to understand the nature of collaboration and ways that it may change over the life of a long-term grant. Interviewees continue to outline benefits for collaboration within INKE while admitting that there continue to be challenges. They also outline several lessons learned which will be applied to the next project.